Dream recall, nightmares, dream sharing, and personality: a replication study - Schredl, Michael; Rauthmann, John (Dreaming, 2022)
Previous research indicated that dream variables such as dream recall, dream sharing, and nightmares are related to personality traits. However, the overall number of studies in this field is rather small, and this data set serves as a necessary replication. Overall, 819 persons (636 women, 183 men) with a mean age of 27.47 ± 9.32 years participated in an online survey. Findings indicated that dream recall was associated with openness to experience, nightmares mainly with neuroticism and—to a smaller extent—with openness to experience, and dream sharing with extraversion. As this pattern of findings is in line with previous research based on other measurement instruments and samples with different characteristics, this demonstrated the robustness of these relationships, supporting the lifestyle hypothesis of dream recall and the continuity hypothesis. Future research can aim at clarifying the causal links between personality characteristics and dream variables. (PsycInfo Database Record (c) 2022 APA, all rights reserved)